A NOVEL REVERSE-PHASE ULTRA-PERFORMANCE LIQUID CHROMATOGRAPHIC METHOD WITH GRADIENT ELUTION FOR SIMULTANEOUS DETERMINATION OF DOLUTEGRAVIR, LAMIVUDINE AND TENOFOVIR DISOPROXIL FUMARATE IN FIXED-DOSE COMBINATION - GAMPA NAGAMALLESWARI; UMA SHANKAR MS (Asian Journal of Pharmaceutical and Clinical Research, 2025)
ABSTRACT Objective: To develop a sensitive and rapid reverse phase ultra-performance liquid chromatographic method for the simultaneous determination of dolutegravir (DTG), lamivudine (LAM), and tenofovir disoproxil fumarate (TDF) with improved separation and stability-indicating features. Methods: Chromatographic separation was performed on an acquity bridged ethyl siloxane/silica hybrid C18 (50 × 2.1 mm, 1.7 μm) column at 40°C using 0.05% trifluoroacetic acid in water (pH 3.0) and methanol as mobile phase, with a flow rate of 0.4 mL/min and ultraviolet detection at 265 nm. The method validation was performed per ICH guidelines and included stress degradation studies. Results: Effective separation was achieved; retention times were 1.25 min for LAM, 2.87 min for TDF, and 3.65 min for DTG. Supporting validation, the limits of linearity were set at 15–90 μg/mL for both LAM and tenofovir, and 2.5–15 μg/mL for DTG, with R2 values exceeding 0.999. Conclusion: The proposed technique provides high accuracy, precision, sensitivity, and specificity in detecting multiple antiretroviral drugs in fixed-dose drug combinations. Compared to previously published methods, the gradient elution profile offers better peak height, greater peak splitting, as well as decreased total time required for analysis. The method’s stability-indicating features, confirmed by forced degradation studies, demonstrate the method’s value for pharmaceutical analysis quality control and stability testing.